Emergency abdominal surgery during a pandemic-related lockdown: a Vietnamese experience - Tran, Loc H.; Nguyen, Hai V.; Chung, Phuong H. (International Surgery Journal, 2026)
Background: The fourth wave of COVID-19 in Vietnam was associated with prolonged lockdown measures that may have influenced access to emergency surgical care. This study evaluated temporal changes in operative volume, prehospital presentation, disease severity, and early postoperative outcomes in common emergency abdominal conditions across distinct pandemic phases. Methods: A retrospective study was conducted at a tertiary referral center, including adult patients undergoing surgery for appendicitis, cholecystitis, peptic ulcer perforation, and bowel obstruction during three periods: social distancing (June–September 2020), lockdown (June–September 2021), and post-lockdown (March–June 2022). Variables included demographic characteristics, prehospital symptom duration, disease severity graded by the American Association for the Surgery of Trauma (AAST) classification, and postoperative complications classified by Clavien–Dindo. Results: A total of 1,251 patients were included. During lockdown, emergency operative volume decreased by approximately 50% compared with the social distancing period. Delayed presentation (>1 day) increased significantly in appendicitis and peptic ulcer perforation (p<0.01), accompanied by higher proportions of AAST Grade III–IV disease in both groups. No significant differences were observed in cholecystitis or bowel obstruction. Postoperative morbidity remained stable overall, except for an increase in moderate-to-severe complications in peptic ulcer perforation during lockdown (p=0.02). After lifting restrictions, operative volume, severity distribution, and early outcomes returned to pre-lockdown patterns. Conclusions: During the lockdown period of Vietnam’s fourth COVID-19 wave, reductions in surgical volume and delayed presentation were observed in selected time-sensitive abdominal emergencies, accompanied by higher anatomic severity and morbidity in perforation cases. These patterns were not observed in the period following restoration of healthcare access.